REFLEXOLOGY AS A COMPLEMENTARY THERAPY FOR REDUCING NAUSEA AND VOMITING IN PEDIATRIC DIARRHEA : LITERATURE REVIEW - Zulva, Siti; Regidor III Dioso; Mohamed Saifulaman Mohamed Said (Rifapublisher.id, 2025)
Background: Diarrhea in children remains a significant global health concern, often accompanied by nausea and vomiting, leading to dehydration and hindered recovery. While oral rehydration solutions and pharmacological therapies are common treatments, the limitations and side effects of the latter have prompted interest in non-pharmacological interventions, such as reflexology. Objective: This literature review aims to explore current evidence regarding reflexology as a complementary therapy for reducing nausea and vomiting symptoms specifically in pediatric patients with diarrhea. Method: A literature review was conducted, analyzing selected articles from databases including Scopus, ProQuest, Clinical Key Nursing, and Sage, covering the years 2020-2025. Keywords used included